Improved pain, physical functioning and health status in patients with rheumatoid arthritis treated with CP-690, 550, an orally active Janus kinase (JAK) inhibitor: results from a randomised, double-blind, placebo-controlled trial. Issue 2 (8th July 2009) - Coombs, J H; Bloom, B J; Breedveld, F C; Fletcher, M P; Gruben, D; Kremer, J M; Burgos-Vargas, R; Wilkinson, B; Zerbini, C A F; Zwillich, S H
Abstract : Objectives: To determine the efficacy of CP-690, 550 in improving pain, function and health status in patients with moderate to severe active rheumatoid arthritis (RA) and an inadequate response to methotrexate or a tumour necrosis factor α inhibitor. Methods: Patients were randomised equally to placebo, CP-690, 550 5, 15 or 30 mg twice daily for 6 weeks, with 6 weeks' follow-up. The patient's assessment of arthritis pain (pain), patient's assessment of disease activity, Health Assessment Questionnaire-Disability Index (HAQ-DI) and Short Form-36 (SF-36) were recorded. Results: At week 6, significantly more patients in the CP-690, 550 5, 15 and 30 mg twice-daily groups experienced a 50% improvement in pain compared with placebo (44%, 66%, 78% and 14%, respectively), clinically meaningful reductions in HAQ-DI (⩾0.3 units) (57%, 75%, 76% and 36%, respectively) and clinically meaningful improvements in SF-36 domains and physical and mental components. Conclusions: CP-690, 550 was efficacious in improving the pain, function and health status of patients with RA, from week 1 to week 6.